2021
DOI: 10.1007/s00415-021-10428-6
|View full text |Cite
|
Sign up to set email alerts
|

Complement inhibition initiated recovery of a severe myasthenic crisis with COVID-19

Abstract: We report on a patient with refractory Myasthenia gravis with acetylcholine receptor antibodies with two prior myasthenic crises suffering from COVID-19 with rapid evolving weakness and respiratory failure. Respiratory failure developed and prolonged mechanical ventilation was necessary. After plasmapheresis, residual, severe generalized and bulbar weakness persisted. Complement inhibition with eculizumab was, therefore, introduced and lead to rapid recovery. In refractory myasthenic crisis individualised ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…After examining the titles and abstracts of the remaining articles, 19 studies with 152 patients with confirmed MG diagnosis and COVID-19 were included in the qualitative systematic review ( Fig. 1 ) [3] , [6] , [8] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Of these studies, 10 were case series, 8 were case reports, and one was a cohort study, as shown in Supplementary Tables 1 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…After examining the titles and abstracts of the remaining articles, 19 studies with 152 patients with confirmed MG diagnosis and COVID-19 were included in the qualitative systematic review ( Fig. 1 ) [3] , [6] , [8] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Of these studies, 10 were case series, 8 were case reports, and one was a cohort study, as shown in Supplementary Tables 1 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“… 3 , 4 , 5 Among 179 patients previously reported, 56% to 100% were hospitalized, and many were intubated. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 It is noteworthy that most of the reported studies were in hospitalized inpatients. Only one study identified patients with COVID‐19 by self‐report.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a clinically significant decrease occurred in MG‐ADL from baseline to 1‐mo follow‐up and was sustained. Eculizumab's rapid onset of action suggests its potential role as a short‐term therapy for myasthenic exacerbation or crisis, as described in case reports, or as bridge therapy to other therapies with slower onset 11,12 . Notably, in two of our patients, eculizumab led to rapid clinical stabilization and facilitated thymectomy for non‐thymomatous MG.…”
Section: Discussionmentioning
confidence: 52%
“…Eculizumab's rapid onset of action suggests its potential role as a short-term therapy for myasthenic exacerbation or crisis, as described in case reports, or as bridge therapy to other therapies with slower onset. 11,12 Notably, in two of our patients, eculizumab led to rapid clinical stabilization and facilitated thymectomy for non-thymomatous MG. Prior to eculizumab, thymectomy had been planned, but deferred due to the patients' unstable clinical status.…”
Section: Discussionmentioning
confidence: 78%